Pengaruh Kebijakan Utang Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun Observasi 2021-2023 - S.E., M.Si, O. Feriyanto; Sabatin, Ngesti Dwi Junita (Economics and Digital Business Review, 2024)
The research results show that partially the Debt to Asset Ratio (DAR) has a negative and significant effect on financial performance which is assumed to be Return on Assets (ROA) in Banking Companies listed on the Indonesia Stock Exchange. This means that the higher the DAR value, the lower the financial performance value indicated by ROA. Partially, it states that the Debt to Equity Ratio (DER) has no significant effect on financial performance (ROE) in banking companies listed on the Indonesia Stock Exchange. This means that the higher the DER value, the inverse effect on ROA. Simultaneously, Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) have a positive and significant effect on financial performance (ROA) in banking companies listed on the Indonesia Stock Exchange.